Investigation of mechanical properties of silver-doped diamond-like carbon coating by varying deposition temperature - Ranjan Kr. Ghadai; G. Shanmugasundar; M. Vanitha; Robert Čep; Soham Das; Bibhu P. Swain (Frontiers in Mechanical Engineering, 2024)
The present work shows the influence of deposition temperatures on the mechanical properties of silver (Ag)-doped diamond-like carbon (DLC) coating synthesized by the thermal chemical vapor deposition (CVD) technique. The deposited film showed excellent mechanical and tribological behavior with respect to the lower deposition temperatures. From the EDS analysis, it was confirmed that the percentage of Ag decreased from 9.8% to 8.4% as the deposition temperature increased. The nanoindentation tests at different loads were extensively carried out to observe the mechanical properties of the coating with respect to various deposition temperatures. The coating hardness (H) and Young’s modulus (E) decreased with the rise in furnace temperature, and the Hmax. and Emax. were observed as 29.71 and 251.19 GPa, respectively, for the Ag-DLC coating grown at 800°C at a load of 20 mN. In comparison to other Ag-DLC thin films made using different deposition techniques, the residual stress (σ) was significantly reduced, reaching 0.45 GPa, which is extremely low.